Anti-gamma-aminobutyric acid B receptor antibody-associated limbic encephalitis in relapsing polychondritis: a rare case report and literature review - Zhang, Jinling; Li, Baiyu; Bao, Lijuan; Zhang, Tianjiao; Zhang, Yishu; Zhang, Minghua; Ren, Taowen (Frontiers in Immunology, 2025)
Relapsing polychondritis (RP) is an immune-mediated disorder that primarily involves the targeting of cartilaginous tissues for inflammation and destruction. Limbic encephalitis (LE) is a rare central nervous system (CNS) manifestation of RP. We report the case of a 39-year-old man who was diagnosed with RP complicated by anti-gamma-aminobutyric acid B receptor (anti-GABABR) antibody−associated LE and presented with recurrent headaches, fever, bilateral auricular swelling, scleral injection, and cognitive impairment. Laboratory tests revealed positive anti-GABABR IgG antibodies in both the serum (titer 1:100) and the cerebrospinal fluid (CSF) (titer 1:1), along with CSF lymphocytic pleocytosis. A brain MRI revealed bilateral frontal and parietal subcortical and periventricular T2-weighted fluid-attenuated inversion recovery (T2-FLAIR) hyperintensities. Immunosuppressive therapy with high-dose methylprednisolone and cyclophosphamide induced rapid symptom resolution, and no relapse occurred during a follow-up period of 1 year. This case expands the spectrum of RP-associated LE, emphasizes the necessity of neuronal autoantibody screening in RP patients with neurological symptoms, and suggests potential pathogenic links involving antigenic cross-reactivity between cartilage and neural tissues and GABAergic metabolism dysregulation.